Christmas sports in St. Kitts-Nevis : our neglected cultural tradition - Mills, F L. ([s.n.] [s.l.]KN, 1984)
Aims to inform nationals what Christmas sports is all about. Contains introductory essay on the historical development of culture in St. Kitts-Nevis and discusses a variety of cultural events. Discusses themes, details, manner of execution, and purpose of cultural Christmas sports. Gives summary of plays, examines origins, describes casts and contains descriptive narrative of sports. Sports include inter alia, `the bull play', `David and Goliath', `Moko-Jumbie', and `masquerade'.